2009
DOI: 10.1016/j.susc.2008.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of N@C60 on Si(100)

Abstract: The interactions between C 60 molecules and the Si(100) surface, as well as the interactions between the endohedrally doped N@C 60 molecules and the Si(100) surface have been explored via ab initio total energy calculations. Configurations which have the cage located upon the dimer row bonded to two dimers (r2) and within the dimer trench bonded to four dimers (t4) have been investigated, as these have previously been found to be the most stable for the C 60 molecule. We show that our results for the adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…The binding energies of these systems are presented in Table 1, alongside the corresponding energies from our previous study [6]; the previous study used a smaller 128 atom Si (100) surface which has been used extensively in other studies [7][8][9][10][11]. As Table 1 illustrates, there appears to be a shift in not only the magnitude of the binding energies, with every configuration becoming less favourable on the larger surface, but the ordering of the favourability hierarchy has also changed.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations
“…The binding energies of these systems are presented in Table 1, alongside the corresponding energies from our previous study [6]; the previous study used a smaller 128 atom Si (100) surface which has been used extensively in other studies [7][8][9][10][11]. As Table 1 illustrates, there appears to be a shift in not only the magnitude of the binding energies, with every configuration becoming less favourable on the larger surface, but the ordering of the favourability hierarchy has also changed.…”
Section: Methodsmentioning
confidence: 96%
“…Thus our model consists of six layers of Si atoms, with the bottom two layers of Si atoms being pinned in their respective bulk; and the bottom layer's dangling bonds are saturated with H atoms (which in turn have been pinned in their own relaxed positions). As with our previous study [6], we have chosen a 2 × 2 tilted dimer reconstruction, as this has been shown to be energetically most favourable within our approach [9]. A large vacuum gap has been included above the Si surface; this vacuum gap ensures a sufficient distance between the top of the fullerene cage(s) and the bottom of the surface for the periodic repeat, so as to minimise the interaction between the two.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plato was used in the first ab-initio studies of the bonding of C 60 molecules to the Si (100) surface that allowed for atomic relaxation [44,45]. Subsequently it has been used to study the adhesion of C 82 molecules and endohedral C 60 molecules and the interaction between C 60 molecules on the Si (100) surface [46,47,48]. In these studies TNDP basis sets were employed, which massively reduced the basis set superposition error to the point where such corrections were unnecessary.…”
Section: Applicationsmentioning
confidence: 99%